The Basic Parameters of Vibration Settings for Sealing Horizontal Surfaces - Nazarenko, Ivan; Ruchynskyi, Mykola; Delembovskyi, Maksym (International Journal of Engineering and Technology, 2018)
Are examined and defined pattern vibratory motion to form horizontal surfaces on the basis of the account of wave phenomena and bias voltages. Given numerical values screeds and rheological characteristics of sealing concrete.Based on the analysis of the energy balance, motion qualities limits are defined. Analytical dependences for the estimation of main parameters of the effective vibroimpact mode are suggested as well as the motion stability layout of the analyzed system is cited.Â Â